Management of established coronary artery disease in aircrew without myocardial infarction or revascularisation. (13th November 2018) - Davenport, Eddie D; Gray, Gary; Rienks, Rienk; Bron, Dennis; Syburra, Thomas; d'Arcy, Joanna L; Guettler, Norbert J; Manen, Olivier; Nicol, Edward D
Abstract : This paper is part of a series of expert consensus documents covering all aspects of aviation cardiology. In this manuscript, we focus on the broad aviation medicine considerations that are required to optimally manage aircrew with established coronary artery disease in those without myocardial infarction or revascularisation (both pilots and non-pilot aviation professionals). We present expert consensus opinion and associated recommendations. It is recommended that in aircrew with non-obstructive coronary artery disease or obstructive coronary artery disease not deemed haemodynamically significant, nor meeting the criteria for excessive burden (based on plaque morphology and aggregate stenosis), a return to flying duties may be possible, although with restrictions. It is recommended that aircrew with haemodynamically significant coronary artery disease (defined by a decrease in fractional flow reserve) or a total burden of disease that exceeds an aggregated stenosis of 120% are grounded. With aggressive cardiac risk factor modification and, at a minimum, annual follow-up with routine non-invasive cardiac evaluation, the majority of aircrew with coronary artery disease can safely return to flight duties.